A CONCEPTUAL MODEL OF LOCATION SELECTION OF BONDED LOGISTICS CENTER SUPPORTING LARGE INDUSTRIES BASED ON A COMBINATION OF FUZZY AHP AND FUZZY TOPSIS - SF, Syafrianita
Free trade in the globalization era has brought rapid and extensive changes to supply chain activities. Raw materials to fulfill industrial needs are not only supplied from within the country but also abroad. The raw materials originating from abroad require storage prior to being used by industry. The bonded logistics center is a location for bonded storage meant for storing goods originating from the outside of the customs area and the ones within the customs area with various facilities provided by the government, as in the suspension of import duties and a storage period of up to three years. The bonded logistics center is a strategic facility that holds an important role within the logistics system, hence the management efficiency is highly dependable on its location. Determining the location of the bonded logistics center is still an issue that is often discussed. This proves quite complex because it involves stakeholders. Selecting the bonded logistics center weighs on several criteria that tend to be subjective and qualitative. This research is aimed at formulating the model of decision-making for selecting the bonded logistics center supporting large industries. A methodology of fuzzy multi-criteria decision-making helps to obtain an effective decision. The fuzzy approach allows a more accurate process of decision-making through the input of human preferences that are vague. As of now, studies that combine the fuzzy technique to weigh the criteria and select the alternative location for the bonded logistics center are still rare. This research combines Fuzzy AHP and Fuzzy TOPSIS to select the location for the bonded logistics center supporting the large industries in West Java. The main input for the application of the multi-criteria decision-making used in this research is the result from the expert respondents’ questionnaire. The criteria and sub-criteria were obtained from the focus group discussion involving academics, business, and government. To overcome the vagueness of the expert’s perception, a linguistic variable and triangular fuzzy number are used. The alternative of the bonded logistics center location within the hierarchical structure was obtained descriptively based on the literature review on industrial areas in West Java.4 The weighting of the criteria and sub-criteria for selecting the location of the bonded logistics center uses Fuzzy AHP. The Fuzzy AHP approach allows a more accurate description of the decision-making process by using comparison ratios. Meanwhile, in determining the location preferences of the bonded logistics center, the study uses Fuzzy TOPSIS. The Fuzzy TOPSIS approach gives various alternatives and criteria used in a decision-making process. The Fuzzy AHP and Fuzzy TOPSIS integration in this research creates a more accurate representation of the relationship among criteria and gives alternatives that support the complex decision-making process in selecting the location of the bonded logistics center to support large industries. The result obtained from using the Fuzzy AHP method, the criteria with the highest to lowest final weight values are regulation, accessibility, cost, property condition, infrastructure service, and economic growth. This research contributes to the conceptual framework for selecting the location of the bonded logistics center with regulations as the criteria being considered. Based on the preference value on the TOPSIS fuzzy technique, the ranking sequence for the bonded logistics center locations is the Jabebeka industrial area, MM2100 industrial area, East Jakarta Industrial Park industrial area, and the Marunda Center industrial area. This study provides an implication for the policy of the bonded logistics centers. For the bonded logistics center holders, it is important for them to pay attention to the location of the bonded logistics centers that are in line with the spatial and regional arrangements. The implications of further research can add a group of freight forwarders in regard to the decision-making when selecting the bonded logistics centers.